Counseling as a means of providing safe social support during the COVID-19 pandemic - Trębski, Krzysztof; Młyński, Józef (Kwartalnik Naukowy Fides et Ratio, 2022)
The COVID 19 outbreak has affected people’s physical and mental health and triggered an avalanche of consequences that many are unable to cope with, and because of the pandemic, even relatives and friends are unable to help in this situation. Many people experience all kinds of difficult situations (such as relationship problems, health, social, educational or economic difficulties) that are not pathological problems but for which individuals are unable to find a suitable solution. Counseling as a helping relationship is a good way for them to gain self-awareness and find the resources they need to make the necessary changes in their lives. The counselors, as professionals in a helping relationship, can help them get through difficult times by providing the necessary support to begin their journey to well-being. The article presents counseling as an opportunity to provide safe social support to people during the COVID 19 epidemic, but also highlights the difficulties this type of service can bring.